Comparative Study on Biological Characteristics and Fruit Quality Changes of Two Citrus Varieties. Issue 3 (April 2020) - Chen, Zhaofang; Wang, Yuxin; Wang, Tie; Li, Sichen; Xiong, Bo; Qiu, Xia; Sun, Guochao; Wang, Zhihui
Abstract: This experiment compared the phenophase, morphological features and fruit quality of the two citrus varieties. The results showed that the whole growth period of Lemon Siranui was about 12 days longer than Siranui. The flowering period, two physiological fruit drop periods and fruit color change period of Lemon Siranui were about 5-7 days later than Siranui. While this study illustrated differences in morphological features that Lemon Siranui tree was stronger than Siranui. And the fruit of Lemon Siranui was heavier than Siranui. It was clear to see that the percentages of soluble solids as well as vitamin C in Lemon Siranui were larger than those in Siranui, which led to better taste qualities. Overall, Lemon Siranui was a new high-quality strain citrus variety with excellent traits which was worth promoting from the analysis of appearance quality and nutritional quality.